Rodrigo Braga: um estudo de arquivos de processos e montagem de exposição - Negrão, Wilson Renato (2017)
The objective of this research is to develop a study of the archives of semiotic-based processes in contemporary art and analyzing the creative process of Rodrigo Braga to investigate the ways of art through this and to understand the artist that transits be-tween different languages. The dissertation will be developed by surveying the evolution of Rodrigo Braga’s career and his emblematic works in the last decades. Covering his sketches, annotations and drawings, even documents in creation process, and by the end, following-up in exhibitions, where the artist will be observed closely, while finishing a work, before opening for public exposure. The result of these analyzes will lead the research meeting some procedural proce-dures that will help to understand the work of Rodrigo Braga. As a new artist, with a career that is still in progress and since his work is in the process of development, the research tends to generate discoveries that are still unpublished, including the artist himself. The studies will focus on his carried out works during the last decades and on the projects which are developed during the research. Through these documents of production process, the trajectories of Rodrigo Braga will be mapped into Brazilian and international artistic context and, thus, to present how much are his works relate to the performance, photography, video, installation and the evolution of his works based on creation process